Effect of early skin- to- skin contact of mother and newborn on mother’s satisfaction - nahidi, fatemeh; Dorri, frogh; Ravari, mahmoud; Akbarzade, Alireza (Advances in Nursing & Midwifery, 2011)
Abstract Background and aim The first minutes after birth are a very vulnerable period for both mother and newborn. The care that is provided during this time is critical to improve their longer-term health. Mother- infant Skin to skin contact immediately after birth creates an optimal environment for the adaptation of newborn infants to extra uterine life and should be a routine method in hospitals. The Purpose of this study was to evaluate the effect of skin to skin contact between newborn and mother immediately after birth on mother’s satisfaction in Taleghani hospital in Arak on 2008–2009. Materials and methods A randomized controlled trial was designed to study the effect of early skin –to- skin contact between mother and newborn. 80 pairs of newborns and their mothers who delivered in Taleghani hospital Arak, Iran were included in the study. They were randomly assigned to two groups (skin to skin contact and routine care). In skin-to-skin contact group, immediately after birth naked newborns were placed in prone position on skin contact with their mothers and in routine care group newborns were placed in cot under warmer. A questionnaire was used to assess mothers’ satisfaction. In the end of breastfeeding mothers’ satisfaction were assessed. Data were collected by a questionnaire, which included questions about the mothers’ satisfaction with the care they received during labor and their tendency to skin to skin contact in future. The validity of questionnaire was determined by content validity method and reliability was obtained by internal consistency (consistency coefficient 0.90). Data were analyzed by SPSS software. Findings A larger proportion of mothers in skin to skin contact group were very satisfied (70%) and satisfied (20%) with their care, and a larger proportion of mothers in routine care group were very unsatisfied (35%) and unsatisfied (35%).There was a significant difference between two groups in terms of their tendency for skin-to-skin contact in future. Conclusion Skin-to-skin contact between mother and newborn results in mother’s satisfaction. Keywords: Mother infant skin to skin contact, mother satisfaction